Nonlinear electrocardiographic leads system transformations - Zaderykhin, O.; Moroz, J. (Видавництво Львівської політехніки, 2010)
This article discusses the problem of electrocardiographic leads transformation. We solve the problem using the method of maximum likelihood for the linear and nonlinear model of transformation. Comparison of derived algorithms quality is present.
Keywords: ECG leads transformation; maximum likelihood; nonlinear model of transformation; electrocardiographic leads reconstruction